The impact of multidrug-resistantMAQ:There is a mismatch in the article title given in the manuscript and title page of PDF. We have followed the manuscript. microorganisms on critically ill patients with cirrhosis in the intensive care unit: a cohort study - Minjee Kim; Filipe S. Cardoso; Anna Pawlowski; Richard Wunderink; Daniela P. Ladner; Juan G. Abraldes; Constantine J. Karvellas (Hepatology Communications, 2023)
The impact of multidrug-resistant (MDR) colonization and MDR infection in critically ill cirrhosis patients remains unclear. We assessed the association of MDR colonization and MDR infection with these patients’ survival. Observational cohort study including adult cirrhosis patients admitted to 5 intensive care units at Northwestern Memorial Hospital (Chicago, Illinois, USA) on January 1, 2010, to December 31, 2017. Patients admitted for elective liver transplant or with previous liver transplant were excluded. Patients were screened for MDR colonization on intensive care unit admission. Infection diagnoses during the intensive care unit stay were considered. The primary endpoint was hospital transplant-free survival. Among 600 patients included, 362 (60%) were men and median (interquartile range) age was 58.0 (49.0, 64.0) years. Median (interquartile range) Model for End-stage Liver Disease, Sequential Organ Failure Assessment, and Chronic Liver Failure—Acute-on-Chronic Liver Failure scores on intensive care unit day 1 were 28.0 (20.0, 36.0), 9.0 (6.0, 13.0), and 55.0 (48.0, 64.0), respectively. Overall, 76 (13%) patients were transplanted and 443 (74%) survived the hospital stay. Infections were diagnosed in 347 (58%) patients: pneumonia in 197 (33%), urinary tract infection in 119 (20%), peritonitis in 93 (16%), bloodstream infection in 99 (16%), Clostridium difficile colitis in 9 (2%), and catheter tip infection in 7 (1%). MDR colonization and MDR infection were identified in 200 (33%) and 69 (12%) patients, respectively. MDR colonization was associated with MDR infection (p < 0.001). MDR colonization or MDR infection was associated with higher number and duration of antibiotics (p < 0.001). Following adjustment for covariables (age, sex, etiology, portal hypertension, and Sequential Organ Failure Assessment score), MDR colonization [OR (95% CI), 0.64 (0.43, 0.95)] or MDR infection [adjusted OR (95% CI), 0.22 (0.12, 0.40)] were independently associated with lower transplant-free survival. Among critically ill cirrhosis patients, MDR colonization or MDR infection portended a worse prognosis.